2011
DOI: 10.1007/s00441-011-1246-y
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β in progression of liver disease

Abstract: Transforming growth factor-β (TGF-β) is a central regulator in chronic liver disease contributing to all stages of disease progression from initial liver injury through inflammation and fibrosis to cirrhosis and hepatocellular carcinoma. Liver-damage-induced levels of active TGF-β enhance hepatocyte destruction and mediate hepatic stellate cell and fibroblast activation resulting in a wound-healing response, including myofibroblast generation and extracellular matrix deposition. Being recognised as a major pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
551
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 621 publications
(568 citation statements)
references
References 104 publications
(118 reference statements)
13
551
0
4
Order By: Relevance
“…TGF‐β activates HSCs and promotes liver fibrosis progression 12. Collagen, TIMP‐1 and α‐SMA are TGF‐β target genes, and are expressed via the JNK and Smad2/3 signalling pathway 13. Our results showed that ADSCs transplantation reduced TAA‐induced JNK and Smad2/3 activation in vivo, with more potent inhibition by transplantation of FGF21_ADSCs than Empty_ADSCs.…”
Section: Discussionmentioning
confidence: 66%
“…TGF‐β activates HSCs and promotes liver fibrosis progression 12. Collagen, TIMP‐1 and α‐SMA are TGF‐β target genes, and are expressed via the JNK and Smad2/3 signalling pathway 13. Our results showed that ADSCs transplantation reduced TAA‐induced JNK and Smad2/3 activation in vivo, with more potent inhibition by transplantation of FGF21_ADSCs than Empty_ADSCs.…”
Section: Discussionmentioning
confidence: 66%
“…TGF-β1, one of the TGF-β isoforms, is the most potent profibrogenic factor. TGF-β signaling promotes fibroblast differentiation into α-smooth muscle actin (α-SMA) expressing myofibroblasts and stimulates collagen deposition after a variety of injuries in tissues, including, among others, the liver (5)(6)(7)(8) and the skin (9). Furthermore, myofibroblastlike cells respond to TGF-β by expressing increased amounts of this factor, thus contributing to fibrosis development through autocrine and paracrine loops of TGF-β-stimulated collagen production (10).…”
mentioning
confidence: 99%
“…To note, the TGF-b is not produced exclusively by the Treg cells, in fact, within inflammatory microenvironment, it is secreted by Kupffer cells and activated hepatic stellate cells, indicating that its reduction not necessarily to reflect the frequency of Treg cells, but rather the improving the hepatic condition [46]. Moreover, CHC patients at the completion of the dietary regimen showed the same trend for the serum levels of HA.…”
Section: Discussionmentioning
confidence: 91%